Designing Rigorous Methods in Integrative Research: Comparing Mindfulness-Based Stress Reduction with the Health Enhancement Program in the Treatment of Urge Urinary Incontinence in Older Adult Women - Felsted, Katarina Friberg (British Journal of Healthcare and Medical Research, 2022)
Older adult women are marginalized in scientific research. Prior research has been done studying the treatment of urinary urge incontinence through mindfulness-based stress reduction. The highest prevalence of urinary urge incontinence is found in older adult women, yet this is the first study to treat older adult women who have urge urinary incontinence with mindfulness-based stress reduction. The methods of a rigorous pilot feasibility and randomized controlled trial are described from study design through completion. Preparations, procedures, and execution of the study including measures, data management, and statistical analyses are delineated. Considerations necessary due to the specific population are explained. Authors discuss significant characteristics, results, and successes and difficulties embedded in the methods used.